A New Study of the History of the Aramaean Kingdoms in View of the Assyrian, Aramaic, and Biblical Texts - Al-weiss, Adnan H.T. (Al-Adab Journal, 2021)
Aramaeans are one of the ancient peoples who migrated from Arabian Peninsula to the fertile Crescent, and who were called (Semites) by western scholars. Although the name Aram was mentioned early in Akkadian documents, scholars agreed that Aramaeans were referred to for the first time in Assyrian texts from the fourteenth century B.C. by the name Ahlamu in Syria and Mesopotamia, especially along Euphrates. After their settlement in cities, they were referred to as Aramu.Aramaeans lived in large areas of Syria and north-west of Iraq. The change of the political situation in the ancient east around 1200 B.C., which resulted in dislocation and political vacuum in Syria and the whole of this ancient area, enabled the Aramaeans to appear as an influential element in the political arena. Since the beginning of the tenth century, they established many states or small kingdoms. The most important ones were Zoba and Bet-Rehub in Lebanon, and Damascus, Hamath, Arpad, Sam'al, and Bet-Adini in Syria.Though the Aramaean Kingdoms were rival, they were united in confederations or coalition, when they were threatened by external force, especially by Assyrian campaigns. These campaigns began before the rise of the Aramaeans kingdoms and were almost continual. At the end of the eighth century B.C, these kingdoms were subjected to Assyrian control.One of the most distinguished aspects of the Aramaean's culture was their language, which was widely used by Assyrians, Babylonians, and Persians along large part of the ancient east. The Aramaeans were also distinct in the trade. The geographical location of their kingdoms among countries and empires enabled them in this aspect.This article is translated by the writer of this Search as a part of his Ph. D. thesis Titled: (The Use of Aramaic in the Neo-Assyrian Empire in the Ninth-Seventh Centuries B.C) P53-58. Submitted to the University of Wales, Britain 1984.